2018
DOI: 10.1186/s13065-018-0469-3
|View full text |Cite
|
Sign up to set email alerts
|

Pyridyl thiosemicarbazide: synthesis, crystal structure, DFT/B3LYP, molecular docking studies and its biological investigations

Abstract: N-(pyridin-2-yl)hydrazinecarbothioamide has been synthesized and characterized by single-crystal X-ray and spectroscopic techniques. Furthermore, its geometry optimization, calculated vibrational frequencies, non-linear optical properties, electrostatic potential and average local ionization energy properties of molecular surface were being evaluated using Jaguar program in the Schrödinger’s set on the basis of the density functional concept to pretend the molecular geometry and predict properties of molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The results revealed that compound 3 showed the least energy gap (ΔE) compared with the other isolated compounds suggesting high chemical reactivity and considerable intramolecular charge transfer from electron donor (HOMO) to electron acceptor (LUMO) groups. 34 Based on this results compound 3 has better bioactivity compared with other reported compounds herein. Additionally, compound 3 has large electronegativity (χeV), global softness (σ eV −1 ), and global electrophilicity (ωeV) compared with other compounds ( Table 6 ).…”
Section: Resultsmentioning
confidence: 58%
“…The results revealed that compound 3 showed the least energy gap (ΔE) compared with the other isolated compounds suggesting high chemical reactivity and considerable intramolecular charge transfer from electron donor (HOMO) to electron acceptor (LUMO) groups. 34 Based on this results compound 3 has better bioactivity compared with other reported compounds herein. Additionally, compound 3 has large electronegativity (χeV), global softness (σ eV −1 ), and global electrophilicity (ωeV) compared with other compounds ( Table 6 ).…”
Section: Resultsmentioning
confidence: 58%
“…All these factors have a significant impact on biological activity, including cell membrane permeability, metal complexation, and inter- and intra-molecular interactions. Since the thiosemicarbazides studied here formally can exist in tautomeric thione (C=S) and thiole (C–S) forms [ 24 , 25 , 55 , 56 ] ( Figure 3 ), we evaluated theoretically their relative Gibbs free energies. For this purpose, geometries of the thione and thiole forms of the thiosemicarbazides were optimized at the DFT level of theory, using the ωB97X-D functional [ 57 ] expressed in the def2-TZVP basis set [ 58 ], as implemented in the Gaussian16 program [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The DFT calculated Mullikan’s atomic charges ( Figure 4 ) revealed charge distribution in individual atoms ( Table S4 ). 27 The HOMO, LUMO and energy gap (ΔE) of the isolated compounds are calculated and given in table. The results revealed that all the compounds have showed the least energy gap (ΔE) suggesting that high chemical reactivity and considerable intramolecular charge transfer from electron donor (HOMO) to electron acceptor (LUMO) groups ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that all the compounds have showed the least energy gap (ΔE) suggesting that high chemical reactivity and considerable intramolecular charge transfer from electron donor (HOMO) to electron acceptor (LUMO) groups ( Figure 6 ). 26 , 27 Additionally, compounds 8 and 9 have large electronegativity (χeV), and global electrophilicity (ωeV) compared to other compounds ( Table S3 and Figure S15 ). 27 Based on the results compounds 8 and 9 may have better bioactivity compared to other reported compounds ( 6 and 7 ) herein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation